The vocational education program at Wagner High School a critical analysis - Barber, Fred T.
The major problem in the research is concerned in determining the nature and analyzing the existing vocational education program at Wagner High School and formulating the most suitable methods for revitalizing existing training opportunities. The study aims: to determine the extent of the present regular curriculum offerings, work-study training and vocational guidance; to establish justifications for implementing and funding an improved program; and to determine the occupations with the best projected employment opportunities.